Hubungan Lamanya Pemakaian Kontrasepsi Suntikan Dengan Kembalinya Kesuburan Pada Post Akseptor Kontrasepsi Suntikan Di Desa Pasir Utama Kecamatan Rambah Hilir - Azmariza, Nana Aldriana, (Jurnal Martenity and Neonatal, 2017)
Injecting contraception is a way to prevent pregnancy through hormonal injection given by Intra Muscular. The types of injectable contraceptives are contraceptive injections of combination type and Depo Progesterone Medroxy Acicate (DMPA). In December 2016, there were 184 injecting contraceptive users in the village of Pasir Utama. This type of injectable contraceptive has several disadvantages. One of them is the delay in the return of fertility after the termination of injectable contraception. The purpose of this study is to determine the relationship between the use of contraceptive injection with the return of fertility in the village of Pasir Utama District Rambah Hilir. This research method is quantitative analytic with cross sectional design. Sampling was conducted by purposive sampling with 60 samples, ie 30 post-acceptor pregnant women with combined injection contraception and 30 pregnant women post-accept with DMPA injection contraception. Data collection was conducted through a guided interview with a checklist instrument. Analysis of research data is univariate analysis and bivariate analysis with T-independent test. The results obtained from the results of statistical tests P value = 0.198 for the relationship between the use of contraceptive injections combination with the return of fertility and P value = 0.491 for the relationship between the use of contraceptive DMPA injections with the return of fertility. The conclusions of this study indicate that there is no correlation between the duration of contraceptive injections combined with the return of fertility in post-contraceptive contraceptive acceptor in Pasir Utama Village Rambah Hilir Subdistrict and no relationship between duration of DMPA injection contraception with the return of fertility in post DMPA contraceptive acceptor post in Pasir Utama Village, Rambah Hilir Sub District.